2005
DOI: 10.1002/ange.200502202
|View full text |Cite
|
Sign up to set email alerts
|

Porous Capsules Allow Pore Opening and Closing That Results in Cation Uptake

Abstract: Knallende Korken: Die protonierten Harnstoffionen (C schwarz, N/O grün), die die Poren einer Polyoxomolybdatkapsel (Mo blau, O rot) verschließen, lassen sich reversibel entfernen, sodass Ca2+‐Ionen (rosa) in die Kapsel eintreten können. Dieser Prozess ähnelt der Funktionsweise gesteuerter Calciumkanäle in Zellmembranen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…According to an X‐ray crystallographic study, as the ionic radius of Ca 2+ is comparable to that of Na + , both are found at approximately the same sites, that is, below the channels of the C 3 axis (Figure 1 a and b) 4. 9, 15 As demonstrated in Figure 5, the lithium ions are completely removed from the capsule when equimolar amounts of CaBr 2 (relative to the overall concentration of Li + ) are added stepwise to solutions of 1 , thus suggesting that besides the effects discussed for Na + ions, the high charge density increases the affinity of each Ca 2+ ion to the three sulfate groups below the pores. Alternatively, depletion of internal Li + sites was achieved with cryptand C211 5…”
Section: Resultsmentioning
confidence: 98%
“…According to an X‐ray crystallographic study, as the ionic radius of Ca 2+ is comparable to that of Na + , both are found at approximately the same sites, that is, below the channels of the C 3 axis (Figure 1 a and b) 4. 9, 15 As demonstrated in Figure 5, the lithium ions are completely removed from the capsule when equimolar amounts of CaBr 2 (relative to the overall concentration of Li + ) are added stepwise to solutions of 1 , thus suggesting that besides the effects discussed for Na + ions, the high charge density increases the affinity of each Ca 2+ ion to the three sulfate groups below the pores. Alternatively, depletion of internal Li + sites was achieved with cryptand C211 5…”
Section: Resultsmentioning
confidence: 98%
“…Closing the pores has important consequences not only for substrate exchange between the inside and outside of the capsules (see below), but also for the capsule stability and the protection of encapsulates. For example, the carbonate-type capsule of the compound (NH 4 ) 72 O is-due to the easy release of CO 2 -only stable for a rather short time at room temperature, while the stability of the capsules increases dramatically after pore closing with formamidinium cations (of course more pro-nounced with guanidinium cations). [61] A similar effect is observed in case of the fluoride-based capsule.…”
Section: Molecular Recognition Of Hydrophobes In Water and Removal Ofmentioning
confidence: 99%
“…The precipitate obtained shows integrated Ca 2 + and pore closing, which decreases the capsule charge and therefore the solubility; this is the correct explanation in contrast to that given in the former paper. [72] The ion-channel activity is retained when the capsules are encapsulated into cationic surfactants though ion uptake/release is slower compared to naked capsules. [35] Important in the context: the related obtained SECs can be integrated into membranes, which allows investigating their ability to act as effective ion carriers.…”
Section: Molecular Recognition Of Hydrophobes In Water and Removal Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter chemical system can formally be compared with the results of the work of Müller et al, who evidenced the multireceptor properties of the twenty pores of Keplerate-type capsules strongly interacting with different substrates such as guanidinium, protonated urea, or amidinium cations. [19] In this context, the DOSY NMR spectroscopy appears to be a powerful method to investigate the plugging-type process in aqueous solution that involves a small "substrate" like NMe 4 + . The compound Na 38 K 3.5 (NMe 4 ) 3.5 [{Mo 6 O 21 (H 2 O) 6 } 12 {Mo 2 -O 2 S 2 (CH 3 COO)} 30 ]·3 CH 3 COO·200 H 2 O, 3, that is, Na 38 K 3.5 -(NMe 4 ) 3.5 3 a·3 CH 3 COO·200 H 2 O, which has recently been reported to contain 3.5 NMe 4 + ions per {Mo 132 S 60 } capsule has the appropriate requirements to study the interactions between the {Mo 9 O 6 S 3 } pores of the capsule with the NMe 4 + cations.…”
Section: H Nmr Spectroscopic Studiesmentioning
confidence: 99%